Matthew Barney and the art of restraint: interactions between body, process and complexity - Monte, Gilmar (Revista do Colóquio, 2025)
This article investigates the relationships between body, resistance and complex thinking in Matthew Barney's series “Drawing Restraint”. Based on Edgar Morin's theoretical framework, we explore how the concept of restraint is mobilized by Barney as an element that generates artistic process, transcending disciplinary boundaries and establishing a poetics of friction. With a multidisciplinary approach that involves sculpture, performance and cinema, the work is analyzed as a complex system in which physical, symbolic and narrative forces operate interdependently. Complex thinking allows us to understand the depth of these relationships, revealing how Barney's art establishes modes of existence traversed by resistance, transformations and creative tensions.